Determinants of stunting in children aged 6-24 months in rural areas: Case control study - Meitriana Pangestuti; Ali Khomsan; Ikeu Ekayanti (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Inappropriate breastfeeding, complementary feeding and repeated infections are direct causes of stunting in children under two years of age. The objective of this research was to investigate the relationship between history of breastfeeding and history of infection with stunting in children living in rural areas who were between the ages of 6 and 24 months old. The research was conducted using a case control study, carried out in the working area of Puring Health Center in 2021 using a sample of 43 children aged 6-24 months taken by simple random sampling. The data were gathered through anthropometric measurements of child’s body length and mother’s height, questionnaire interviews for history of breastfeeding and infection, and the examination of Maternal and Child Health (MCH) book. The chi-square test and multiple logistic regression were utilized in the analysis that was carried out. The final results suggested that stunting was caused by gender (p= 0,032), mothers’s height (p= 0,032), and food parenting pattern aged 6-8 months (p= 0,026). Food parenting pattern aged 6-8 months was the most dominant factor associated with stunting (p=0,026 AOR 5,17 95% CI:1,22-21,95). In conclusion, gender, mother’s height, and food parenting pattern aged 6-8 months were significantly associated with stunting.